2009
DOI: 10.1080/00268970903078559
|View full text |Cite
|
Sign up to set email alerts
|

Feature selection method based on fuzzy entropy for regression in QSAR studies

Abstract: Feature selection and feature extraction are the most important steps in classification and regression systems. Feature selection is commonly used to reduce the dimensionality of datasets with tens or hundreds of thousands of features, which would be impossible to process further. Recent example includes quantitative structureactivity relationships (QSAR) dataset including 1226 features. A major problem of QSAR is the high dimensionality of the feature space; therefore, feature selection is the most important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…QSAR models using different descriptors and modeling approaches for the target systems studied in the current work have been reported using the same datasets. Three studies for TS-1 (Elmi et al, 2009;Yi et al, 2008), one for TS-2 (Queiroz et al, 2011), two for TS-3 (Hu et al, 2009), and one each for TS-4 (Garg et al, 1999) and TS-5 (Debnath, 1999) were identified and studied for comparative performance with PMF-PLS QSAR. Note that for TS-6 no QSAR modeling study could be identified.…”
Section: Resultsmentioning
confidence: 99%
“…QSAR models using different descriptors and modeling approaches for the target systems studied in the current work have been reported using the same datasets. Three studies for TS-1 (Elmi et al, 2009;Yi et al, 2008), one for TS-2 (Queiroz et al, 2011), two for TS-3 (Hu et al, 2009), and one each for TS-4 (Garg et al, 1999) and TS-5 (Debnath, 1999) were identified and studied for comparative performance with PMF-PLS QSAR. Note that for TS-6 no QSAR modeling study could be identified.…”
Section: Resultsmentioning
confidence: 99%
“…In recent yeares, several QSAR and QSPR models have been used based on both linear and non-linear methods that aimed to predict different activities and properties [60][61][62][63][64][65][66][67][68][69][70][71] .…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning and feature selection methods have been widely used in QSAR models . Levatić et al applied semisupervised learning in QSAR models.…”
Section: Introductionmentioning
confidence: 99%